Use of jackfruit (Artocarpus heterophyllus Lam.) as an agroindustrial byproduct in animal feeding: A systematic review - Ortega-González, Liliana; Ayala-Martínez, Maricela; González-Tenorio, Roberto; Nova-Morales, Gerardo Manuel; Hernández-Domínguez, Héctor; Soto-Simental, Sergio (Agronomía Mesoamericana, 2025)
Introduction. Currently, food industry innovation results in the generation of thousands of tons of organic waste that negatively impacts environmental sustainability. Therefore, it is important to implement actions that contribute to waste reduction and utilize bioactive compounds effectively. Objective. To conduct a systematic literature review on the nutrients and bioactive compounds present in the main components of jackfruit (peel, pulp, and seed), to evaluate its potential incorporation into livestock feed. Development. A systematic review was conducted based on experimental articles retrieved from ScienceDirect, Wiley, Google Scholar, Scopus, and Springer Link databases. A specific search equation was employed for this purpose. Results demonstrated that different jackfruit components contain nutrients (proteins, carbohydrates, minerals) and bioactive compounds (polyphenols, flavonoids, polysaccharides, phenols, etc.) that have demonstrated positive effects when incorporated into livestock feed (broilers, sheep, and goats). Conclusions. The incorporation of jackfruit into animal feed promotes weight gain, improves digestibility, stimulates the immune system, and reduces feed production costs.